The Policy Responses towards Contemporary Islamic Capital Market in Indonesia: The Dynamics and Challenges - Andri Soemitra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
Islamic capital market has been developed to anticipate the need for capital management in the Islamic industry that grows rapidly. This paper will study the dynamics and the contemporary challenges of capital market industry products. The research utilizes a qualitative approach by searching data and information from relevant literatures, specific data, and information from regulators. The researcher conducts analytical studies literature after collecting and compiling data from relevant literatures. This study shows that Islamic capital markets have attempted to reach certain standards based on the criteria of Islamic teaching. However, this study found that globally and nationally the development of Islamic capital markets is still struggling with regulatory, products, and practices problems. This study indicates that the Islamic capital market regulator in Indonesia still needs wider socialization and more efforts to increase the low level of literacy and inclusion. Â Pasar modal syariah dikembangkan untuk mengantisipasi kebutuhan pengelolaan modal di industri syariah yang tumbuh pesat. Tulisan ini mengkaji dinamika dan tantangan kontemporer produk industri pasar modal. Penelitian ini menggunakan pendekatan kualitatif dengan mencari data dan informasi dari literatur yang relevan dan data dan informasi spesifik dari regulator. Peneliti melakukan studi analitik literatur setelah mengumpulkan dan menyusun data dari literatur yang relevan. Studi ini menunjukkan bahwa pasar modal syariah telah berusaha mencapai standar tertentu berdasarkan kriteria ajaran Islam. Namun, penelitian ini menemukan bahwa secara global dan nasional perkembangan pasar modal syariah masih berkutat dengan masalah regulasi, produk dan praktik. Hasil penelitian ini menunjukkan bahwa regulator pasar modal syariah di Indonesia masih membutuhkan usaha-usaha sosialisasi yang lebih luas untuk meningkatkan literasi dan inklusi pasar modal syariah yang masih rendah di Indonesia.Â